Attitudes toward migration on the Ecuadorian border - Calvo Rodríguez, Vanessa Mercedes Villarreal Villarreal, Andrés Fabricio Subía Arellano, Diana Carolina Montero Medina, Robin Williams (Opción, 2020)
This study aims to analyze the difference in the attitudes toward migrants that haveEcuadorians living in the border city of Tulcán, compared with the attitude of those wholive in the city of Quito. The instrument used was the Scale of Attitudes TowardsImmigrants EAPI (by its Spanish acronym) designed by Subía, A.; Arroyo, D.; Montero,D. and Cedeño, X. (2019). Findings show that there is a statistically significantrelationship between the variables: level of education, knowledge of the differencebetween voluntary migration and forced migration, place of residence of local citizensand the attitude of rejection towards migrants.